In vitro effect of low intensity laser on the cytotoxicity produced by substances released by bleaching gel - Caroline Maria Gomes Dantas; Carolina Lapaz Vivan; Leila Soares Ferreira; Patricia Moreira de Freitas; Márcia Martins Marques (Sociedade Brasileira de Pesquisa Odontológica, 2010)
This in vitro study aimed to analyze the effect of different parameters of phototherapy with low intensity laser on the viability of human dental pulp fibroblasts under the effect of substances released by bleaching gel. Cells were seeded into 96 wells plates (1 x 10³ cells/well) and placed in contact with culture medium conditioned by a 35 % hydrogen peroxide bleaching gel for 40 minutes, simulating the clinical condition of the in-office bleaching treatment. Cells cultured in ideal growth conditions served as positive control group (PC), and the cells grown in conditioned medium and non-irradiated served as negative control group (NC). Cells grown in conditioned medium were submitted to a single irradiation with a diode laser (40 mW, 0.04 cm²) emitting at visible red (660 nm; RL) or near infrared (780 nm; NIR) using punctual technique, in contact mode and energy densities of 4, 6 or 10 J/cm². The cell viability was analyzed through the MTT reduction assay immediately and 24 hours after the irradiation. The data was compared by ANOVA followed by the Tukey's test (p < 0.05). The cell viability increased significantly in 24 hours within each group. The PC presented cell viability significantly higher than NC in both experimental times. Only the NIR/10 J/cm² group presented cell viability similar to that of PC in 24 hours. The phototherapy with low intensity laser in defined parameters is able to compensate the cytotoxic effects of substances released by 35 % hydrogen peroxide bleaching gel.